Визначення ефективності стратегії технічного обслуговування керуючої системи з мажоритарною структурою - Мандзій, Б. А.; Волочій, Б. Ю.; Озірковський, Л. Д.; Змисний, М. М.; Кулик, І. В. (Видавництво Львівської політехніки, 2011)
The object of consideration is a fault-tolerant control system based on majoritarian structure with maintenance. Such systems used to control of radio electronic system of responsible use and operation of long-term. Modeling fault-tolerant systems implemented using the technology of analytical modeling. The possibilities of modeling behavior of fault-tolerant systems based on the developed models is shown.
Keywords: control system; reliability; fault-tolerant system; majority structure